Handbook of Organization Theory and Management The Philosophical Approach Second Edition - JACK RABIN , T. Aaron Wachhaus, Jr. (Taylor & Francis Group, 2006)
This is the second edition of the Handbook, again addressed to uniting philosophy and public administration. Few subjects are more influenced by philosophy than the form of governance a public selects to guide and administer its public affairs. Yet, the literature continues to be strangely silent about the relation between the two. It continues to be our hope that this book will inspire many more efforts to explore this most important of relationships, especially because the real work has only just begun. In the 21st century, it is particularly appropriate to build such bridges from the past to the future and to rediscover our roots while contemplating our intellectual progress. Originally, the first edition of this book grew out of a doctoral seminar conducted by Thomas D. Lynch at Florida Atlantic University. Concerned by a lack of integrated literature on philosophical and epistemological foundations of modern organization and political theory, Dr. Lynch enlisted one of his Ph.D. students, Todd J. Dicker, to jointly develop a work in which potential authors, who had already made significant contributions to the literature on their topics and had established reputations as thinkers and scholars, could contribute to a project that analyzed public administration’s intellectual roots. The first edition of the Handbook, published in 1998, proved to be extremely popular, and at the dawn of the 21st century, a revision and expansion was proposed. An important update was the addition of another one of Dr. Lynch’s Ph.D. students from FAU, Dr. Peter L. Cruise, as coeditor of the second edition. It is he who gladly assumed the many tasks required of producing this revised and expanded book.